PENGEMBANGAN STANDARD OPERATING PROCEDURE AKUNTASI DAN PENENTUAN BIAYA STANDAR PADA PETERNAKAN BEBEK PETELUR DESA TULUSAYU - Rahayu, Anita; Indrawati, Novy Karmelita (Manajemen & Bisnis Jurnal, 2019)
This development aims to assist Peternakaan Bpk. Nur Samiaji in the making Standart Operating Procedure (SOP)/Work Instruction(WI) Accounting and standard cost determination at Peternakan Bebek Milik Bpk. Nur Samiaji in Desa Tulusayu. The method is development. Model of development uses Design Based Research (DBR) method. Using these 6 stages of research and development to small scale trials. The procedure are problem identification, outlining objectives, developing design and development, product testing, evaluation of trial tests, and communicating test results. The result of this development are Standart Operating Procedure (SOP) and Work Instruction (WI) with total 2 SOP and 19 WI. academic validator give average value 3 for 2 SOPs dan 19 WIs. And practitioners validator give average value 4 for 2 SOPs dan 19 WIs. That values show that Standart Operating Procedure (SOP) and Work Instruction (WI) are feasible applied at Peternakaan Bebek Petelur milik Bpk. Nur Samiaji Di Desa Tulusayu. Keyword: SOP, Accounting, Standard Cost